Very Low Temperature Epitaxy of Heavily In Situ Phosphorous Doped Ge Layers and High Sn Content GeSn Layers. (13th December 2016) - Aubin, J.; Hartmann, J. M.; Barnes, J. P.; Pin, J. B.; Bauer, M.
Abstract : We have studied in the 300–350°C temperature range, the 100 Torr epitaxy of heavily in-situ phosphorous doped Ge and high Sn content GeSn alloys in a 200 mm industrial Reduced Pressure - Chemical Vapor Deposition tool. We have first of all quantified the impact of the phosphine (PH3 ) flow on the structural and electrical properties of Ge:P layers. To that end, we have used a dedicated low temperature Ge precursor, digermane (Ge2 H6 ), in order to promote P incorporation. We have reached very high atomic and electrically active P concentrations, at most 5 × 10 20 cm −3 and 7.5 × 10 19 cm −3, respectively. We have then evaluated the impact of the Ge2 H6 and SnCl4 flows on the GeSn growth kinetics at 325°C, 100 Torr. As expected, the GeSn growth rate increases almost linearly with the Sn concentration, from 5 up to 21 nm.min −1 . The Sn atoms seem to catalyze H desorption from the surface, resulting in higher GeSn growth rates, then. Finally, we have studied the impact of temperature, in the 300–350°C range, on the GeSn growth kinetics. The GeSn growth rate exponentially increases with the temperature, from 15 up to 32 nm.min −1 . The associated activation energy is low, e.g. Ea = 11 kcal.mol −1 . Really high Sn concentrations (at most 15%) were obtained in smooth, single crystalline layers.